Model-Driven Development and Operation of Multi-Cloud Applications The MODAClouds Approach - Di Nitto, Elisabetta; Matthews, Peter; Petcu, Dana; Solberg, Arnor (SpringerBriefs in Applied Sciences and Technology, 2017)
Communications Engineering, Networks; Computer Communication Networks; Software Engineering; Computational Intelligence